Quantification of tolvaptan in rabbit plasma by LC-MS/MS: Application to a pharmacokinetic study - Kumar S. Moola; Bala Sekhara Reddy Challa; Chandrasekhar Kothapalli Bannoth (Elsevier, 2015)
A sensitive, selective and high-throughput liquid chromatography-tandem mass spectrometry (LC-ESI-MS/MS) method was developed and validated for the quantitation of tolvaptan in rabbit plasma. Sample clean-up involved liquid-liquid extraction (LLE) and chromatography was performed on Zorbax SB C18 analytical column (50 mm×2.1 mm, 3.5 µm) using 0.1% formic acid:methanol (20:80, v/v) as the mobile phase. The parent→product ion transitions for the drug (m/z 449.2→252.1) and IS (m/z 456.2→259.2) were monitored on a triple quadrupole mass spectrometer, operating in the multiple reaction monitoring (MRM) and positive ion mode. The method was validated over the concentration range of 0.10-1000.00 ng/mL and successfully applied to a pharmacokinetic study of healthy rabbits.